Antiapolipoprotein A-1 Autoantibody Positivity Is Associated with Threatened Abortion. (7th March 2020) - Vecchié, Alessandra; Bonaventura, Aldo; Carbone, Federico; Maggi, Davide; Ferraiolo, Antonella; Carloni, Beatrice; Andraghetti, Gabriella; Affinito Bonabello, Laura; Liberale, Luca; Fetaud, Vanessa; Pagano, Sabrina; Dallegri, Franco; et al.
Abstract : Background . Autoantibodies against apolipoprotein A-1 (anti-ApoA-1 IgG) were demonstrated to be associated with cardiovascular outcomes in several inflammatory diseases. As balanced inflammation is critical for uncomplicated pregnancy, we aimed to investigate the prevalence of anti-ApoA-1 IgG and anti-c-terminal ApoA-1 autoantibodies (Ac-terAA1 IgG) in a cohort of pregnant women and their potential relationship with threatened abortion (TA). Methods . Between 2012 and 2014, 371 consecutive outpatient pregnant women were included in this study and followed until delivery. Anti-ApoA-1 and anti-Ac-terAA1 IgG were measured by ELISA technique on serum samples collected between the 24 th and 26 th week of pregnancy. Associations with TA were tested using linear regression analysis and C-statistics. Results . Median age was 34 with a prevalence of the Caucasian ethnicity (90.5%). TA occurred in 10 women (2.7%). C-statistics indicated that anti-ApoA-1 and anti-Ac-terAA1 IgG levels upon study inclusion were predictive of TA (0.73, 95% confidence interval [CI] 0.69-0.78, p < 0.001 and 0.76, 95% CI 0.71-0.80, p = 0.01, respectively). At the prespecified anti-ApoA-1 IgG cutoff, the negative predictive value (NPV) was 100%. For anti-Ac-terAA1 IgG, at the optimal cutoff, the NPV was 99%. Linear regression models indicated that risk associations were independent of age and the presence of autoimmune diseases for both autoantibodies (p < 0.001 ). Anti-Ac-terAA1 IgG-positive individuals were more frequently non-Caucasians (p = 0.009 ). Conclusion . Anti-ApoA-1 and anti-Ac-terAA1 IgG are independently associated with TA during pregnancy with an appealing NPV. The causal biological mechanisms underlying this association as well as the possible clinical relevance of these findings require further investigations.